Prognosis of Dilated Cardiomyopathy with Severe Heart Failure according to Functional Classification Scales in Childhood - Araújo,Fátima Derlene da Rocha (2018)
Abstract Background: Heart failure is the main manifestation of dilated cardiomyopathy in childhood, and the systematic evaluation of signs and symptoms allows monitoring the treatment outcome. Objective: To evaluate the use of three functional classification scales of heart failure in children and adolescents with dilated cardiomyopathy. Methods: Longitudinal and observational study including patients from zero to 18 years with dilated cardiomyopathy and severe initial heart failure. All of them were followed up using the New York Heart Association (NYHA), The New York University Pediatric Heart Failure Index (The NYU PHFI) and Ross version 2012 scales. Statistical analyzes were done using Statistical Package for Social Science, version 14.0, with Mann-Whitney test, Chi-Square test or Fisher's test, application of the Operating Characteristic Curve, Wilcoxon test and Kappa coefficient for comparison of scales and Kaplan-Meier curve for survival evaluation. The level of significance adopted was 5%. Results: A total of 57 patients, aged from 1 to 200 months (mean of 48.7 ± 55.9) and follow-up of 6 to 209 months (mean of 63.6 ± 48.4) were included. There was substantial agreement between the Ross 2012 scales, The NYU PHFI and NYHA (Kappa = 0.71 and 0.82, respectively). Paired analysis by the Wilcoxon test, comparing the scales before and after treatment, was significant (p < 0.0001). The greatest survival was found in patients with class I/II by NYHA or scores lower than 11 points in the others. Conclusion: The use of functional assessment scales of heart failure proved to be useful in the follow-up and evaluation of the therapeutic response and there was no difference between them. Patients who remained in functional classification III or IV NYHA or scores ≥ 11 in Ross 2012 or The NYU PHFI had worse prognosis.